Enhancing the Formation and Implementation of Sustainability Strategies Using the Balanced Scorecard: Evidence from the Chemical Industry - Fülöp, G.; Hernádi, B.; Jalali, M.; Meidute-Kavaliauskiene, I.; Ferreira, F. (Handbook of Research on Global Competitive Advantage through Innovation and Entrepreneurship, 2015)
Given the strategic challenges of the 21st century, it becomes fundamental to determine strategic alternatives for sustainability. This chapter aims to contribute to the successful formation and implementation of corporate strategies for sustainability and business excellence, through the development and application of an extended Balanced Scorecard (BSC), which includes the social and environmental perspectives. We outline the structure for a Sustainability Balanced Scorecard (SBSC) as well as the steps required for its development. Elements for each of the different sustainability strategies of the SBSC are proposed and, finally, a case study of the formation and introduction of a “credible” sustainability strategy in the chemical industry is presented. The results demonstrate the usefulness of the SBSC in pursuing sustainability strategies, and provide evidence that the introduction of such a system is likely to lead to fundamental changes in the way a company is managed. Practical implications and managerial guidelines are also presented.